140 Obesity as a modifiable risk factor in repaired tetralogy of fallot. (May 2019) - Cassar, Mark Philip; Orchard, Elizabeth; Jones, Alex; Neubauer, Stefan; Hudsmith, Lucy; Rider, Oliver
Abstract : Introduction: In modern society, obesity is an increasingly prevalent, and now widely recognised, risk factor for almost all cardiovascular diseases, exerting independent adverse effects on the cardiovascular system. Despite this, the effects within adult congenital heart disease are not well documented but are becoming increasingly important. Methods: We collected data from 155 patients (aged 7–76 years) with repaired tetralogy of Fallot (rTOF), scanned between 2004 and 2018 in OCMR. Anthropometric data (height, weight, age) were recorded. All patients had CMR imaging (1.5T) to determine right ventricular (RV) cavity size (end diastolic volume; EDV; ml) and phase contrast flow imaging to determine pulmonary regurgitation severity (PR, %). The association of obesity with RVEDV in rTOF was determined by linear regression and compared to the relationship seen in the normal heart (n=722) using dummy variable regression. Results: Comparing rTOF patients scanned in the period 2013–2018 (n=67) to those of 2002–2012 (n=88) showed a substantial increase over time in the proportion of rTOF patients who were either overweight (19.4% to 28.4%) or obesity (9.4% to 13.6%, figure A). In parallel, the proportion of patients who were underweight declined (19.4% to 6.8%). As height (167±13 vs 166±11cm, p=0.66) and age (32±15 vs 28±14 yr, p=0.16) did not differ between the groups, the 6 kg greater average weight in the later population can be attributed to fat mass. Strikingly, 42% of rTOF patients scanned in the last five years were either overweight or obese, highlighting this is a significant clinical problem. In rTOF, RV dilatation was associated with increased BMI, regardless of the presence or severity of PR (figure B). Although dilatation of the RV was associated with higher BMI in the normal population, the degree of RV cavity dilatation is over four-fold greater in rTOF (RVEDV rTOF +21 ml, vs. normal heart +5 ml per 10 BMI points increase, p<0.01, figure C). In comparison, although obesity results in LV cavity dilation in both rTOF and normal hearts, there was no difference in the degree of cavity dilatation (LVEDV rTOF +8 ml vs +6 ml per 10 BMI points increase, p=0.79 for comparison). This suggests that the RV dilatory response to obesity in rTOF is disproportionate, being not only over two-fold greater than the dilatory response of the LV within rTOF patients, but also four-fold higher than that seen in the normal heart. Conclusion: Obesity is becoming more prevalent in rTOF patients and is related to disproportionate dilatation of the RV, at all levels of pulmonary regurgitation. The reasons for this are unknown but are likely to be related to the additional stroke volume demands of obesity imposed in the setting of a congenitally pathological ventricle. Chronic PR and existing RV dilatation contribute too. Given the relationship between RV dilatation, symptoms and the need for surgical intervention, this should logically be detrimental in rTOF. It follows then that treatment strategies that reduce RV cavity size in rTOF may be beneficial. As such, obesity is a promising and modifiable therapeutic target in rTOF. Conflict of Interest: None